External male genital trauma caused by firearm projectile. Case report. - Vásquez-Sullca, Roy R. (2021)
External genital trauma is caused by external mechanical agents and account for 68.1% of all genitourinary trauma. Firearm projectile trauma are increasing as a result of escalating delinquency in urban settings, these traumas involve the scrotum and penis in 78% and 28%, respectively. Management of these traumas require evaluation of the scrotum and penis; orchiectomy is needed if the testes are not recuperable. Surgical procedures are aimed at avoiding complications such as sexual and urinary dysfunction. We present two cases aimed at reporting the management of external genital trauma at our centre in absence of local reports of firearm projectile trauma.